The influence of accounting students’ perception of public accounting profession: A study from Indonesia - Laksmi, Ayu Chairina; Al Hafis, Savero Izkha (Journal of Contemporary Accounting, 2019)
Public accounting profession is one of prestigious and important professions in Indonesia. Recent data, however, show that the number of public accountants in Indonesia is very small compared to the population. Thus, accounting students’ perception regarding the public accounting profession needs to be investigated. This study aims to investigate the influence of accounting students’ perception of public accounting profession toward their interest to the public accounting profession. A sample of 100 students from three different universities in Indonesia were used as respondents. The results demonstrate that financial rewards, professional recognition, labour market considerations and professional training positively influence the interests of accounting students to become a public accountant. The results also indicate that working environment, social values and personality have no influences on accounting students’ interest to become a public accountant.